KOMPETENSI TUTOR KESETARAAN PAKET C DAN HASIL BELAJAR WARGA BELAJAR PADA PUSAT KEGIATAN BELAJAR MASYARAKAT - Puji Hadiyanti (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
Community learning center (PKBM) tutors should have professional pedagogic, personal and social competencies. This study aimed at investigating whether the tutors in PKBM Miftahul Jannah, East Jakarta have such competencies. This study also investigated the learners. achievement . A survey using questionnaire was conducted for that purpose. This study reveals that the tutors have such competencies whereas the learners' achievement vary. This study also provides suggestions to improve the tutors quality.